Uncovering Deterministic Behavior of Black Hole IGR J17091–3624: A Twin of GRS 1915+105 - Anindya Guria; Banibrata Mukhopadhyay (The Astrophysical Journal)
Understanding the nonlinear properties in accreting systems, particularly for black holes, from observation is illuminating as they are expected to be general relativistic magnetohydrodynamic flows that are nonlinear. Two commonly used features associated with nonlinear systems are chaos, which is deterministic, and randomness, which is stochastic. The differentiation between chaotic and stochastic systems is often considered to quantify the nonlinear properties of an astrophysical system. Particular emphasis is given to the fact that data are often noise contaminated and finite. We examine the dual nature of the black hole X-ray binary IGR J17091–3624, whose behavior has been closely studied in parallel to GRS 1915+105. Certain similarities in the temporal classes of these two objects have been explored in the literature. However, this has not been the case with their nonlinear dynamics: GRS 1915+105 shows signs of both determinism and stochasticity, while IGR J17091–3624 was found to be predominantly stochastic. Here, we confront the inherent challenge of noise contamination faced by previous studies, particularly Poisson noise, which adversely impacts the reliability of nonlinear results. We employ several denoising techniques to mitigate noise effects, and employ methods like principal component analysis, singular value decomposition, and correlation integrals to isolate the deterministic signatures. We find signs of determinism in IGR J17091–3624, thus supporting the hypothesis of it being similar to GRS 1915+105, even as a dynamical system. Our findings not only shed light on the complex nature of IGR J17091–3624 but also pave the way for future research employing noise-reduction techniques to analyze nonlinearity in observed dynamical systems.